2010
DOI: 10.1159/000319501
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Urethral Strictures: A Brief Review of the Current Surgical Treatment

Abstract: A review of the recent literature on the surgical management of anterior urethral stricture was performed. The literature was searched via PubMed using the search terms ‘urethral stricture’ and ‘urethroplasty’ from 1996 to 2009. The management of anterior urethral strictures is changing rapidly in the sense that the reconstructive procedures have evolved greatly. Penile skin, because of its location and because it is hairless, has been popular and used for a long time. Since the early 1990s, buccal mucosa graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 171 publications
(141 reference statements)
3
39
0
3
Order By: Relevance
“…On the contrary, urethroplasty was traditionally considered a difficult surgical procedure and reserved for much more complex cases, although advanced with better longterm cure rates (Singh et al, 2011). However, it has been demonstrated that endoscopic surgery was superior to urethroplasty as long as the stricture did not exceed 2 cm in length, given its low morbidity and rapid convalescence (Wright et al, 2006;Hameed et al, 2011;Veeratterapillay and Pickard, 2012;Tinaut-Ranera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, urethroplasty was traditionally considered a difficult surgical procedure and reserved for much more complex cases, although advanced with better longterm cure rates (Singh et al, 2011). However, it has been demonstrated that endoscopic surgery was superior to urethroplasty as long as the stricture did not exceed 2 cm in length, given its low morbidity and rapid convalescence (Wright et al, 2006;Hameed et al, 2011;Veeratterapillay and Pickard, 2012;Tinaut-Ranera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of techniques have been described for the treatment of the anterior urethra, including dilations, urethrotomy, end-to-end urethroplasty, graft urethroplasty, flap urethroplasty and two-stage urethroplasty; success rates depend on the study and the type of treatment. 8,9 Surgical treatment of the posterior urethra (including bulbar urethra) is more standardized and is generally related to the length of the stricture. A urethrotomy is preferred if the length is less than 1 cm, and a urethroplasty is indicated when the length is greater than 1 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Published online 19 Urethral reconstructive surgery has always been a challenging part for urologist since the dawn of our speciality. In this book leading experts in lower urinary reconstructions from all over the world present their views and experience in that field, together with practical tips and tricks.…”
Section: Publisher Intechmentioning
confidence: 99%
“…Current enthusiasm for the technique was promoted by Duckett 1986, (8) Burger and associates 1992 (9), Dessanti and colleagues 1992 (10) and Elkasaby et al (11) In the following years, numerous reports had described successful use of buccal mucosal graft in the repair of urethral defects associated with previously failed hypospadias surgery and those associated with urethral stricture. (12)(13)(14)(15)(16)(17)(18)(19) Nowadays, buccal mucosa has become the mainstay of these tissue transfer techniques. (13) In February 2006, Simonato et al (20) described the results of the first pilot study on the use of the tongue as an alternative donor site for graft urethroplasty with good functional and aesthetic results.…”
mentioning
confidence: 99%